Study of Stability of Personal Dosimeter - Baghdad Science Journal (مجلة بغداد للعلوم)
The study is carried out by using personal dosimeters (film badge). The films are irradiated to absorbed dose of range (0.01-10000 rad). The calibration curves are drawn by using the ordinary method taking into account the filtration effects in three regions (D (Pb/Sn),D(Du),D(300). The calibration films are stored in ambient condition. It is found that the optical density increases, which is attributed to the photodegradation of the films may induce localized states in the energy gap causing increasing in optical absorption, but optical density decreases, which attributed to the photodegradation of the films may cause some cracks at the film surface during the first month, whereas at the rest months we see clear stability in optical density for the irradiated films. Before irradiation, there is increasing in optical density during the second month, and decreasing in optical density during the rest months. It is concluded that aging effects must be considered for personal dosimeter before and after irradiation to know its use ability as a permanent record.